The efficacy of endoxifen in treating borderline personality disorder in young female patients: reports of two cases - Singh, Tanu (International Journal of Basic & Clinical Pharmacology, 2025)
This case reports presents two young female patients diagnosed with borderline personality disorder (BPD) who were treated with endoxifen. The report details their clinical presentations, previous treatment histories, the rationale for initiating endoxifen as adjunctive therapy, and the subsequent clinical outcomes. The objective is to understand the efficacy and safety of endoxifen in managing BPD symptoms, focusing particularly on impulsivity, mood fluctuations, and overall functional recovery.